Introducing public edible landscapes as a key component of the urban agricultural framework - Bailey, Erin Kay (Kansas State University, 2018)
In our ever-growing urban environments food security is dwindling. Healthy food may be difficult to find in city centers, but publicly owned land is still common. In many cities, a significant percentage of green space is publicly accessible and regularly maintained. Under appropriate circumstances these green spaces can be utilized to grow edible food and benefit the cities and communities they are placed in. Claims of the benefits of public edible landscapes include: beautification, strengthening communities, food security, ecological services, self-sufficiency, education and may lead to a more positive attitude towards urban agriculture. Existing organizations working with public edible landscapes in three US municipalities of varying size were used as case studies to explore strategies and challenges in proposing, implementing and maintaining public edible spaces. Interviews were conducted with representatives from the Beacon Food Forest in Seattle, WA, the Dr. George Washington Carver Edible Park in Asheville, NC, and the Upper Valley Apple Corps in Hartford, VT. These case studies identified common concepts related to the success of public edible landscapes: a presence of community interest, actively involved individuals with a skill set in food production, the presence of an umbrella or advocacy organization, and support from city officials. A discussion of approaches being used by others could provide the foundation for future research into the effects of introducing edible plants into public green space on the local community and environment.
Keywords: Public green space; Edible landscape; Community; Urban agriculture